2018
DOI: 10.18203/2320-6012.ijrms20183625
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension and its risk factors among school teachers in Dhaka, Bangladesh

Abstract: Background: School teachers in urban area are experiencing sedentary life style behaviors. This study was aimed to determine the prevalence and risk factors of hypertension (HTN) among school teachers in Dhaka city.Methods: This cross-sectional study was carried out from May to October of 2017. Total 323 school teachers in Dhaka city aged between 25-59 years were enrolled using cluster random sampling technique. Data on socio-demographic profile, different risk factors, co-morbidities, family history and blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 19 publications
4
8
2
Order By: Relevance
“…The bar chart (Figure 1) shows the WHO/ISH blood pressure classification of respondents, with optimal, normal blood pressure classifications and mild hypertension (grade 1) having higher percentages. The prevalence of hypertension among respondents, using the WHO/ISH classification as seen in Table 5 waist circumference alone, in this study was higher than that found in several studies done in US, Bangladesh and South Africa [12,21,22].…”
Section: Resultscontrasting
confidence: 77%
See 1 more Smart Citation
“…The bar chart (Figure 1) shows the WHO/ISH blood pressure classification of respondents, with optimal, normal blood pressure classifications and mild hypertension (grade 1) having higher percentages. The prevalence of hypertension among respondents, using the WHO/ISH classification as seen in Table 5 waist circumference alone, in this study was higher than that found in several studies done in US, Bangladesh and South Africa [12,21,22].…”
Section: Resultscontrasting
confidence: 77%
“…This is not surprising, as according to the WHO, the African region had the highest prevalence of hypertension among the six WHO regions [26]. The prevalence in this study was however lower than that among teachers in Dhaka, Bangladesh and South Africa whose prevalence exceeded both the values recorded by WHO for low and middle income countries [12,16,21]. However, low and middle income countries like Nigeria and other African countries as well as Indo-Asian countries like Bangladesh have been shown to bear the highest burden of hypertension globally.…”
Section: Resultssupporting
confidence: 43%
“…The prevalence found in this study was much lower than the 21.3% reported in Port-Harcourt, South-South Nigeria (Ordinioha, 2013) but very close to the study conducted in among lecturers in Mbarara Uganda in which prevalence was found to be 7.7% (Amanyire et al, 2019). In contrast, a higher prevalence of 52% among lecturers in Dhaka, Bangladesh (Barua et al, 2018), and 44% at Hawassa University in Ethiopia (Esaiyas et al, 2018).The lower prevalence of hypertension found in this study may be due to the fact that the participants exhibited good health-seeking behavior and good lifestyle.…”
Section: Discussionsupporting
confidence: 63%
“…The prevalence of hypertension in this study was lower than the national prevalence (35.2%) [ 46 ], the African subregional prevalence (47.5%) [ 47 ], and the prevalence of the studies done in Nigeria (36.6%) [ 48 ], in Bangladesh (52%) [ 49 ], in Zambia (40%) [ 50 ], in Ghana (42.4%), and in South Africa (46%) [ 51 ]. However, it was higher than that of the studies done in Northern Ethiopia (18.1%) [ 52 ], in Bahir Dar, northwest Ethiopia (16.45%) [ 16 ], in Jimma, Southwest Ethiopia (13%) [ 53 ], in Addis Ababa (21%) [ 17 ], in Durame town, Southern Ethiopia (22.4%) [ 54 ], and in Owerri, Nigeria (12.4%) [ 55 ].…”
Section: Discussionmentioning
confidence: 66%